Legal Justice Analysis in the Court Decision on the Urban Light vs. Love Light Artwork Copyright Dispute - Disemadi, Hari Sutra; Agustianto, Agustianto; Sofia, Sofia (Actual Insight, 2025)
This study aims to analyze the principles of legal justice embodied in Decision Number 31/Pdt.Sus-Hak Cipta/2020/PN.Niaga.Jkt.Pst., concerning the copyright dispute between the artwork “Urban Light” by Chris Burden and the “Love Light” installation at Rabbit Town. The research employs a normative juridical method, utilizing statutory and case approaches to examine the relevance of Law Number 28 of 2014 on Copyright and its application in the court’s judgment. The data used are secondary, comprising legislation, court decisions, and related legal literature, analyzed descriptively and qualitatively. The findings reveal that the panel of judges has duly considered distributive, commutative, and procedural justice by providing comprehensive protection of the moral and economic rights of the creator. The decision affirms that unauthorized reproduction and adaptation of copyrighted works constitute infringement, ensuring a balanced consideration of the rights of creators and users. Furthermore, this ruling is expected to serve as a significant precedent for copyright protection in Indonesia and to enhance public legal awareness regarding the importance of respecting intellectual property rights.